Molecular Profile of the HepG2 Tumor Cell Line - Arzumanian, V.A.; Pyatnitsky, M.A.; Vakhrushev, I.V.; Ptitsyn, K.G.; Radko, S.P.; Zgoda, V.G.; Kiseleva, O.I.; Poveryennaya, E.V. (Biomedical Chemistry: Research and Methods, 2024)
Cell lines are widely used in scientific research due to their accessibility, stability, and functional similarity to the original cells. The HepG2 line, being the fourth most popular cell culture, is often used in toxicological and metabolic studies due to its partial retention of hepatocyte properties.In our study, the molecular portrait of the HepG2 cell culture was constructed for the first time. To build this portrait, we used previously obtained data for a single sample, including results of whole-genome sequencing (WGS), whole-genome bisulfite sequencing (WGBS), transcriptome (RNA-seq), translatome (Polysome-seq), and proteome (LC-MS/MS) profiling. For the assessment of HepG2 cell line heterogeneity, we analyzed whole-genome and transcriptome data published in the NCBI SRA database, as well as proteome research results available in the PRIDE resource.Our study showed that the HepG2 cell line generally demonstrates a high degree of stability at the genomic and transcriptomic levels; however, samples from China require closer attention when transferring the results of transcriptomic and proteomic experiments. The HepG2 genotype is characterized by stable chromosomal rearrangements, such as translocation between the short arms of chromosomes 1p and 21p, tetrasomy of chromosome 20, loss of the short arm of all SAT chromosomes, and the long arm of the Y chromosome. Despite the absence of 1216 protein-coding genes at the genomic level, 12,602 genes are expressed at the transcriptomic level, of which only 10,461 are detected at the translatome level, and only 1027 genes are identified at the proteome level, which is related to the limitations of mass spectrometry sensitivity. As a result of the omics data analysis, we presented a detailed molecular portrait of the HepG2 cell culture, illustrating the omics profile at various levels for each gene.